Emotional intelligence, sociodemographic, and investment decision: the moderating effect of financial literacy - Puspita, Nindi Vaulia; Mansor, Aida Azlina; Yuliari, Kartika (Manajemen dan Bisnis, 2023)
This study aims to determine the effect of emotional intelligence, sociodemographic factors on investment decisions, and financial literacy as moderating variables of emotional intelligence and sociodemographic factors on investment decisions. The research population is investor saham pemula (ISP) community, a sample of 106 investors. The analysis technique used in this research uses the help of the Smart PLS 3.0 data processing application. the results of the study indicate that Emotional Intelligence has a positive and significant effect on investment decisions; Sociodemography has no effect on investment decisions; Emotional intelligence is positive and significant to investment decisions moderated by financial literacy; positive and significant sociodemography on investment decisions moderated by financial literacy